(untitled) (Research, Society and Development, 2022)
Objective: to identify in the scientific production the actions developed by nurses in the Mobile Emergency Care Service. Method: Scope review with database search: Medical Literature Analysus and Retrieval System Online (MEDLINE), Latin American and Caribbean Health Sciences Literature (LILACS), Scientific Electronic Library Online (SCIELO), Database Nursing (BDENF), and the National Library of Medicine (PubMed), using controlled descriptors, from 2017 to 2021, in Portuguese, English and Spanish. Results: study composed of 17 articles, originating two themes. Conclusion: the results allow an overview of the nurse’s performance over time, verifying its transformations, the advances achieved, the current state constituted and its future projection. Furthermore, the studies made it possible to clarify the real activities performed by nurses at SAMU, explain the obstacles they face in their professional practice and, on the other hand, reaffirm their role in this area of ​​activity.